Clinical Utility of Atrioventricular Coupling Index in Cardiovascular Disease - Shuxuan Qin; Li Zhang; Mengmeng Ji; Zhenni Wu; Yixia Lin; Qing He; Mingxing Xie; Yuman Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Atrioventricular coupling refers to the synchronized interaction between the atrial and ventricular phases of contraction and relaxation within the cardiac cycle. Atrioventricular coupling can be assessed by the left atrioventricular coupling index and right atrioventricular coupling index. These indices provide a comprehensive assessment of the functional interdependence between the atrial and ventricular chambers, and offer insights into cardiac performance beyond traditional markers. Atrioventricular coupling indices are critical for aiding in risk stratification and clinical decision‐making, ultimately improving patient outcomes. This review focuses on the clinical utility of atrioventricular coupling in various cardiac pathologies.